Scientific Mapping of Global Research Trends on Jain Philosophy: A Bibliometric Analysis - Pal, Suman; Kumar, Vinod; Kumar, Virendra (Journal of Data Science, Informetrics, and Citation Studies)
This paper presents a bibliometric analysis of research work done in the global academic world concerning Jain philosophy and its knowledge system. In this study, a total of 3346 publications related to Jain philosophy freely available on 'Lens Database published from the year 1961 to 2024 (16/09/2024, 4:00 PM) have been analyzed with the help of VOSViewer Software (1.6.20 edition), which is freely available. The study results show that the highest numbers of publications related to Jain philosophy (867) were published during 2021-2025. Jeffrey D. Long (307 publications) and Pankaj Jain (305 publications) are ranked first and second among the most productive authors related to Jain philosophy. In contrast, Timothy R. Oton (4428 citations) and Christopher W. Moore (1731 citations) are ranked first and second respectively among the top Cited authors. The most trending keywords in Jain philosophy-related studies are India, Philosophy, Jainism, Ethics, and Religion. The most Cited source is 'The International Journal of Advanced Manufacturing Technology' and the most productive source is 'The Indian Journal of Philosophy'.
Keywords: Jain Philosophy; VOSViewer; Lens Database; Bibliometric Analysis and Scientific Visualization.